Cost benefit analysis of computerized radiography system in a tertiary care hospital - Pimpalwar, Yayati; Rao, Akhilesh; Shukla, Yashasvi (International Journal of Research in Medical Sciences, 2017)
Background: Computed radiography (CR) has presently proven to be both efficient and cost effective as against conventional radiography. Cost benefit and cost effectiveness analysis of a newly installed computerized radiography system in comparison with Conventional radiography set-up in a tertiary care hospital. Methods: Costs incurred under major heads were calculated and compared for both Computerized and Conventional radiography systems. A brief survey regarding the overall clinician and patients response towards the newly installed CR system was carried out and results were calculated. Results: CR system proves to be highly efficient tool in the department of radiology to provide not only better quality images and faster means of image acquisition and archiving but also higher rates of satisfaction amongst radiology staff, clinicians and patients. Overall cost-effectiveness as well as the consumer satisfaction of the new technology is good as compared to conventional radiography. CR reduces repetition of images due to artifacts caused by dark room procedures and due to the provision of multiple images on a single film an average reduction in film expenditure. It reduces waiting period for patients and increases level of satisfaction in clinicians working in critical care dept. and A&E dept. due to early processing of urgent films. Conclusions: cost benefit analysis of CR over conventional radiography proved overall running costs are comparable to the conventional system with a breakeven point achievement in a couple of years since installation especially in a high turnover tertiary care health setup.